Formation of aluminium, aluminium nitride and nitrogen clusters via laser ablation of nano aluminium nitride. Laser Desorption Ionisation and Matrix-Assisted Laser Desorption Ionisation Time-of-Flight Mass Spectrometry - Panyala, Nagender Reddy; Prysiazhnyi, Vadym; Slavíček, Pavel; Černák, Mirko; Havel, Josef (Rapid communications in mass spectrometry, 2011)
Laser Desorption Ionisation (LDI) and Matrix-Assisted Laser Desorption Ionisation (MALDI) Time-of-Flight Mass Spectrometry (TOFMS) were used to study the pulsed laser ablation of aluminium nitride (AlN) nano powder. The formation of Al(m)(+) (m=1-3), N(n)(+) (n=4, 5), AlN(n)(+) (n=1-5, 19, 21), Al(m)N(+) (m=2-3), Al(3)N(2)(+), Al(9)N(n)(+) (n=5, 7, 9, 11 and 15), Al(11)N(n)(+) (n=4, 6, 10, 12, 19, 21, 23, and 25), and Al(13)N(n)(+) (n=25, 31, 32, 33, 34, 35, and 36) clusters was detected in positive ion mode. Similarly, Al(m)(-) (m=1-3), AlN(n)(-) (n=1-3, 5), Al(m)N(-) (n=2, 3), Al(2)N(n)(-) (n=2-4, 28, 30), N(n)(-) (n=2, 3), Al(4)N(7)(-) Al(8)N(n)(-) (n=1-6), and Al(13)N(n)(-) (n=9, 18, 20, 22, 24, 26, 28, 33, 35, 37, 39, 41 and 43) clusters were observed in negative ion mode. The formation of the stoichiometric Al(10) N(10) cluster was shown to be of low abundance. On the contrary, the laser ablation of nano-AlN led mainly to the formation of nitrogen-rich Al(m)N(n) clusters in both negative and positive ion mode. The stoichiometry of the Al(m)N(n) clusters was determined via isotopic envelope analysis and computer modelling.